Evolution of Neuropsychological Deficits in First-Ever Isolated Ischemic Thalamic Stroke and Their Association With Stroke Topography: A Case-Control Study. Issue 6 (9th March 2022) - Scharf, Anne-Carina; Gronewold, Janine; Todica, Olga; Moenninghoff, Christoph; Doeppner, Thorsten R.; de Haan, Bianca; Bassetti, Claudio L.A.; Hermann, Dirk M.
Abstract : Background: The thalamus plays an essential role in cognition. Cognitive deficits have to date mostly been studied retrospectively in chronic thalamic stroke in small cohorts. Studies prospectively evaluating the evolution of cognitive deficits and their association with thalamic stroke topography are lacking. This knowledge is relevant for targeted patient diagnostics and rehabilitation. Methods: Thirty-seven patients (57.5±17.5 [mean±SD] years, 57% men) with first-ever acute isolated ischemic stroke covering the anterior (n=5), paramedian (n=12), or inferolateral (n=20) thalamus and 37 in-patient controls without stroke with similar vascular risk factors matched for age and sex were prospectively studied. Cognition was evaluated using predefined tests at 1, 6, 12, and 24 months. Voxel-based lesion-symptom mapping was used to determine associations between neuropsychological deficits and stroke topography. Results: Patients with anterior thalamic stroke revealed severe deficits in verbal memory (median T score [Q1–Q3]: 39.1 [36.1–44.1]), language (31.8 [31.0–43.8]), and executive functions (43.8 [35.5–48.1]) at 1 month compared with controls (verbal memory: 48.5 [43.6–61.0], language: 55.7 [42.3–61.1], executive functions: 51.3 [50.1–56.8]). Patients with paramedian thalamic stroke showed moderate language (44.7 [42.8–55.9]) and executive (49.5 [44.3–55.1]) deficits and no verbal memory deficits (48.1 [42.5–54.7]) at 1 month compared with controls (59.0 [47.0–64.5]; 59.6 [51.1–61.3]; 52.5 [44.2–55.3]). The language and executive deficits in paramedian thalamic stroke patients almost completely recovered during follow-up. Intriguingly, significant deficits in verbal memory (44.7 [41.5–51.9]), language (47.5 [41.8–54.1]), and executive functions (48.2 [46.2–59.7]) were found in inferolateral thalamic stroke patients at 1 month compared with controls (50.5 [46.7–59.9]; 57.0 [51.2–62.9]; 57.4 [51.2–60.7]). Language, but not executive deficits persisted during follow-up. Voxel-based lesion-symptom mapping revealed an association of verbal memory deficits with anterior thalamus lesions and an association of non-verbal memory, language, and executive deficits with lesions at the anterior/paramedian/inferolateral border. Conclusions: All 3 stroke topographies exhibited significant deficits in diverse cognitive domains, which recovered to a different degree depending on the stroke localization. Our study emphasizes the need for comprehensive neuropsychological diagnostics to secure adequate patient rehabilitation.